Outcome of surgery in advanced ovarian cancer varies between geographical regions; opportunities for improvement in The Netherlands. Issue 8 (August 2019) - Timmermans, M.; Sonke, G.S.; Slangen, B.F.M.; Baalbergen, A.; Bekkers, R.L.M.; Fons, G.; Gerestein, C.G.; Kruse, A.J.; Roes, E.M.; Zusterzeel, P.L.M.; Van de Vijver, K.K.; Kruitwagen, R.F.P.M.; et al.
Abstract: Introduction: The care for patients with epithelial ovarian cancer(EOC) is organised in eight different geographical regions in the Netherlands. This situation allows us to study differences in practice patterns and outcomes between geographical regions for patients with FIGO stage IIIC and IV. Methods: We identified all EOC patients who were diagnosed with FIGO stage IIIC or IV between 01.01.2008 and 31.12.2015 from the Netherlands Cancer Registry. Descriptive statistics were used to summarize treatment and treatment sequence(primary cytoreductive surgery(PCS) or neoadjuvant chemotherapy and interval cytoreductive surgery(NACT-ICS)). Moreover, outcome of surgery was compared between geographical regions. Multilevel logistic regression was used to assess whether existing variation is explained by geographical region and case-mix factors. Results: Overall, 6, 741 patients were diagnosed with FIGO IIIC or IV disease. There were no differences in the percentage of patients that received any form of treatment between the geographical regions(range 80–86%, P = 0.162). In patients that received cytoreductive surgery and chemotherapy, a significant variation between the geographical regions was observed in the use of PCS and NACT-ICS(PCS: 24–48%, P < 0.001). The percentage of complete cytoreductive surgeries after PCS ranged from 10 to 59%( P < 0.001) and after NACT-ICS from 37 to 70%( P < 0.001). Moreover, geographical region was independently associated with the outcome of surgery, also when adjusted for treatment sequence( P < 0.001). Conclusion: We observed a significant variation in treatment approach for advanced EOC between geographical regions in the Netherlands. Furthermore, the probability to achieve no residual disease differed significantly between regions, regardless of treatment sequence. This may suggest that surgical outcomes can be improved across geographical regions.